The Emerging Roles of NDR1/2 in Infection and Inflammation - Ye, Xiaolan; Ong, Naomi; An, Huazhang; Zheng, Yuejuan (Frontiers in Immunology, 2020)
The nuclear Dbf2-related (NDR) kinases NDR1 and NDR2 belong to the NDR/LATS (large tumor suppressor) subfamily in the Hippo signaling pathway. They are highly conserved from yeast to humans. It is well known that NDR1/2 control important cellular processes, such as morphological changes, centrosome duplication, cell proliferation and apoptosis. Recent studies revealed that NDR1/2 also play important roles in the regulation of infection and inflammation. In this review, we summarized the roles of NDR1/2 in the modulation of inflammation induced by cytokines and innate immune response against the infection of bacteria and viruses, emphasizing on how NDR1/2 regulate signaling transduction through Hippo pathway-dependent and -independent manners.